Stem Cell-Based Cell Therapy for Spinal Cord Injury - Byung Gon Kim (Cell Transplantation, 2007)
Traumatic injuries to the spinal cord lead to severe and permanent neurological deficits. Although no effective therapeutic option is currently available, recent animal studies have shown that cellular transplantation strategies hold promise to enhance functional recovery after spinal cord injury (SCI). This review is to analyze the experiments where transplantation of stem/progenitor cells produced successful functional outcome in animal models of SCI. There is no consensus yet on what kind of stem/progenitor cells is an ideal source for cellular grafts. Three kinds of stem/progenitor cells have been utilized in cell therapy in animal models of SCI: embryonic stem cells, bone marrow mesenchymal stem cells, and neural stem cells. Neural stem cells or fate-restricted neuronal or glial progenitor cells were preferably used because they have clear capacity to become neurons or glial cells after transplantation into the injured spinal cord. At least a part of functional deficits after SCI is attributable to chronic progressive demyelination. Therefore, several studies transplanted glial-restricted progenitors or oligodendrocyte precursors to target the demyelination process. Directed differentiation of stem/progenitor cells to oligodendrocyte lineage prior to transplantation or modulation of microenvironment in the injured spinal cord to promote oligodendroglial differentiation seems to be an effective strategy to increase the extent of remyelination. Transplanted stem/progenitor cells can also contribute to promoting axonal regeneration by functioning as cellular scaffolds for growing axons. Combinatorial approaches using polymer scaffolds to fill the lesion cavity or introducing regeneration-promoting genes will greatly increase the efficacy of cellular transplantation strategies for SCI.